2009
DOI: 10.1143/jjap.48.08he01
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mask and Necking Deformation on Bowing and Twisting in High-Aspect-Ratio Contact Hole Etching

Abstract: The effects of mask characteristics on high-aspect-ratio contact hole (HARC) etching profiles were investigated. The evaluation of etching profiles produced with different taper angle masks confirmed that the bowing amount and mask selectivity worsened with decreasing mask taper angle. The relationship between mask taper angle and distribution of scattered ion flux on the sidewall of a tapered mask was calculated. The scattered ion flux was heavily concentrated in the upper part of the sidewall in the case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…Bowing primarily results from the change in the acceptance angle of incident ions into the feature due to erosion of mask material and subsequent reflection from the facets of resist, diffusive particle scattering within the feature or scattering from rough surfaces. 2,6 Maintaining CDU requires minimizing pattern distortion, in which an initially circular mask opening is not preserved through the depth of the feature, evolving into ellipses or other noncircular shapes. [7][8][9] CER originates from nonuniformities in the mask due to stochastic processes during etching or from the lithography-development process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bowing primarily results from the change in the acceptance angle of incident ions into the feature due to erosion of mask material and subsequent reflection from the facets of resist, diffusive particle scattering within the feature or scattering from rough surfaces. 2,6 Maintaining CDU requires minimizing pattern distortion, in which an initially circular mask opening is not preserved through the depth of the feature, evolving into ellipses or other noncircular shapes. [7][8][9] CER originates from nonuniformities in the mask due to stochastic processes during etching or from the lithography-development process.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Maintaining CDU also requires minimizing twisting, where the etch does not proceed strictly normal to the surface but deviates from the normal, and avoiding feature-to-feature variations in the total etch depth. 6,11 Many of these problems associated with CDU can be attributed to the stochastic nature of fluxes of radicals and ions incident into adjacent features. With the CDs of features now less than 10 nm and the mask opening having a commensurately smaller area, the number and variety of particles incident into adjacent features is subject to statistical noise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For precise control etching processes, it is strongly required to measure and evaluate etched shapes precisely. Existing semiconductor metrology methods, such as CD-SEM 4 and OCD 5 , are not suitable for measurement of HAR structures due to the nature of their probes.…”
Section: Introductionmentioning
confidence: 99%
“…They gave evidence supporting that the redeposition of particles sputtered from the mask slope on the contact-hole sidewall results in sidewall necking, and the secondary etching of the sidewall by ions reflected from the mask slope contributes to the formation of sidewall bowing. Miyake et al 17 investigated the effect of mask tapering on bowing during high-aspect-ratio contact-hole etching. They observed that bowing and mask etching rate increased with decreasing taper angle of the mask.…”
mentioning
confidence: 99%